Electron‐Transfer Photochromism To Switch Bulk Second‐Order Nonlinear Optical Properties with High Contrast1. (2nd September 2014) - Li, Pei‐Xin; Wang, Ming‐Sheng; Zhang, Ming‐Jian; Lin, Chen‐Sheng; Cai, Li‐Zhen; Guo, Sheng‐Ping; Guo, Guo‐Cong
Abstract The first bulk electron‐transfer photochromic compound with intrinsic second‐order nonlinear optical (NLO) photoswitching properties has been synthesized. This system employs an electron‐transfer photoactive asymmetric viologen ligand coordinated to a zinc(II) center.